Loss of Microtubule-Associated Protein 2 Immunoreactivity Linked to Dendritic Spine Loss in Schizophrenia - Shelton, Micah A. (Biol Psychiatry, 2015)
BACKGROUND: Microtubule-associated protein 2 (MAP2) is a neuronal protein that plays a role in maintaining dendritic structure through its interaction with microtubules. In schizophrenia (Sz), a number of studies have revealed that MAP2’s typically robust immunoreactivity (IR) is significantly reduced across several cortical regions. Previous studies have not explored the relationship between MAP2-IR reduction and lower dendritic spine density, which is frequently reported in schizophrenia nor has MAP2-IR loss been investigated in the primary auditory cortex (Brodmann Area 41), a site of conserved pathology in Sz. METHODS: Using quantitative spinning disk confocal microscopy in two cohorts of Sz subjects and matched control subjects (Sz, n=20; C, n=20), we measured MAP2-IR as well as dendritic spine density and spine number in deep layer 3 of BA41. RESULTS: Sz subjects exhibited a significant reduction in MAP2-IR. The reductions in MAP2-IR were not associated with neuron loss, loss of MAP2 protein, clinical confounders, or technical factors. Dendritic spine density and number were also reduced in Sz and correlated with MAP2-IR. Twelve (60%) Sz subjects exhibited MAP2-IR values lower than the lowest values in controls; only in this group were spine density and number significantly reduced. CONCLUSIONS: These findings demonstrate that MAP2-IR loss is closely linked to dendritic spine pathology in Sz. Because MAP2 shares substantial sequence, regulatory, and functional homology with MAP tau, the wealth of knowledge regarding tau biology and the rapidly expanding field of tau therapeutics provide resources for identifying how MAP2 is altered in Sz and possible leads to novel therapeutics.